Feeding Strategy and Management Practices of Indigenous Chicken in Barishal District of Bangladesh - Mahbuba Sultana; Nasim Al Mamun; Faisal Kabir; Mehedi Islam Moon; Falguni Baroi; Md. Tabedar Rosul Noyon (Turkish Journal of Agriculture: Food Science and Technology)
A threshold survey was conducted at five upazillas of Barishal district in Bangladesh namely Babuganj, Barishal Sadar, Banaripara, Agaljhara and Gouronodi to know the socioeconomic status of respondents, flock structure, feeding strategy, production performances and management practices of indigenous chicken. Primary data were collected and analyzed through descriptive statistics by using IBM SPSS version 20.0. Women were highly engaged (75.68%) in rearing indigenous chicken than male (24.32%). Average age of respondents in the study area was 35.32 year. Occupations of respondents were 69.52% housewife, 12.74% agriculture, 9.24% business, 4.84% students, and 1.82% day laborer. Educational qualification mainly primary (50.24%), high school (33.16%), college (3.62%), university (1.22%) and illiterate (11.14%). Average number of flock size was 24.05, where cocks 172, hens 4.26, pullets 4.04 and chicks were 15.89. The mean body weights of cocks were 1.40 kg, hens 1.33kg, and chicks were 24.91g. Egg production per bird per clutch was 13.07 and clutch number per year was 3.55. Rearing system of indigenous chicken was 75% semi intensive, 13.2% free range and 11.9 % intensive. Poultry houses were made by bamboo, wood, tin (22.5%), concrete, tin (19.5%), wood, net (51.9%), wire net, and tin (6.3%). About 31.3% respondents kept only chicken in the house and 68.8% used to kept bird miscellaneously. Highest percentages (90%) of farmers have facilities to utilized scavengable feed resources base (SFRB) around the surroundings. About 23.15% framers supplied commercial feed, 53.8% household grains, 15% hand mixed feed, and 5.6% SFRB where 2.5% supplied no feed to the birds. About 31.28% farmers supplied 50g feed per day. Only 31.9% respondents regularly vaccinate their birds. About 33.1% respondents used antibiotic to their flock. In present findings 73.1% flocks affected with various diseases where 31.9% affected with Newcastle diseases (ND), 36.9% Fowl Cholera and 31.3% with other diseases. Finally it can be concluded that better management practices, feeding strategies, disease control measures can utilize the merit of indigenous chicken.